PENGARUH PETA BERPIKIR (MIND MAP) TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 KOTA PEKANBARU - Sundari, Imas; Zulkifli, Zulkifli; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the effect of mind map on the ability to read the beginning of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru. The research used experimental method with pretest posttest control group design. The population in this study were children aged 5-6 years, amounting to 90 children and the sample used were 30 children divided into two classes, experimental class and control class. The data collection technique used is observation. Technique of data analysis using t-test by using program of SPSS 20. The research hypothesis is that there is influence of the use of mind map to the ability of reading the beginning of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru. Based on data analysis known t hitung = 11,929> t table = 2.086 with Sig. (2-tailed) = 0.000. because Sig <0,05 hence can be concluded that there is difference of reading ability of beginning before and after use mind map. Can be interpreted that there is influence map of mind to ability of reading beginning of child age 5-6 years in TK Negeri Pembina 3 Pekanbaru significant equal to 66,12%Keywords: Reading the Beginning, Mind Map